Blood Cytokine, Chemokine and Gene Expression in Cholestasis Patients with Intractable Pruritus Treated with a Molecular Adsorbent Recirculating System: A Case Series - Luiz F Lisboa; Sonal Asthana; Andreas E Kremer; Mark Swain; Sean M Bagshaw; Noel Gibney; Constantine J Karvellas (Canadian Journal of Gastroenterology)
BACKGROUND: The molecular adsorbent recirculating system (MARS) is an albumin-dialysis modality that has been investigated predominantly in patients with acute and acute-on-chronic liver failure.